"Стрільці" давньоруських літописів - Терещенко, О. (Сiверянський лiтопис, 2009)
У статті розглядаються час та обставини появи терміну “стрільці” на сторінках давньоруських літописів; розкривається смислове навантаження терміну та регіональні особливості його вживання. На матеріалі писемних джерел подається короткий нарис історії військових формувань кінних лучників у воєнних кампаніях давньоруських князівств XI-XIII ст. В статье рассматриваются время и обстоятельства появления термина “стрельцы” на страницах древнерусских летописей; раскрывается смысловая нагрузка термина и региональные особенности его употребления. На материале письменных источников даётся краткий очерк истории формирований конных лучников в военных кампаниях древнерусских княжеств XI-XIII вв. The article deals with the time and circumstances of the appearance of the term “striltsy” in the annals of Ancient Rus; the author investigates the semantic sense of this term and local peculiarities of its usage. Using the materials of the written sources, the author gives brief essay of the history of the units of mounted archers at the military campaigns of Ancient Rus principalities from XI to XIII century.